2018
DOI: 10.1509/jmr.15.0509
|View full text |Cite
|
Sign up to set email alerts
|

How Deviations from Performance Norms Impact Charitable Donations

Abstract: Although the actions of others can influence a consumer's behavior, these actions are often at odds with performance norms. For example, charities can experience relatively low rates of support (resulting in a negative deviation from a performance norm) or relatively high rates of support (resulting in a positive deviation from a performance norm). Previous research provides evidence of the equivocal effects of these deviations, with both positive and negative deviations motivating prosocial behaviors. The cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Participants then reported their CRM engagement by answering the following three questions (White & Peloza, 2009): “How likely are you to purchase the mug?,” “How inclined are you to purchase the mug?,” and “How willing are you to purchase the mug?” (1 = not at all to 7 = very likely ; Cronbach’s α = .97). Our choice of the dependent variable is consistent with prior CRM studies (Allen et al, 2018; White et al, 2011; White & Peloza, 2009).…”
Section: Methodsmentioning
confidence: 85%
“…Participants then reported their CRM engagement by answering the following three questions (White & Peloza, 2009): “How likely are you to purchase the mug?,” “How inclined are you to purchase the mug?,” and “How willing are you to purchase the mug?” (1 = not at all to 7 = very likely ; Cronbach’s α = .97). Our choice of the dependent variable is consistent with prior CRM studies (Allen et al, 2018; White et al, 2011; White & Peloza, 2009).…”
Section: Methodsmentioning
confidence: 85%
“…Type of influences. Normative influences reflect whether certain behavior, such as the support of an issue, is acceptable (e.g., Cialdini, Reno, and Kallgren 1990), and prior research has shown that these pressures influence socially responsible behaviors (Allen, Eilert, and Peloza 2018;Cialdini, Reno, and Kallgren 1990;Nolan et al 2008). Companies can create such pressures by institutionalizing the issue within the organization (e.g., adopting policies providing benefits for samegender spouses or policies promoting diversity).…”
Section: Corporate Activist Strategies To Remove Barriersmentioning
confidence: 99%
“…Individual Differences. Individual differences are strong predictors of prosocial behaviors; those high in interdependent self-construal (Winterich and Barone 2011; Duclos and Barasch 2014;Allen, Eilert, and Peloza 2018;Simpson et al 2018), moral identity (Aquino and Reed 2002;Reed and Aquino 2003;Aquino et al 2007Aquino et al , 2011Winterich et al 2013;Reed et al 2016), collective self-esteem (Shang et al 2008), religiosity (Stavrova and Siegers 2014), and public self-consciousness (White and Peloza 2009) are more likely to behave prosocially. Moreover, those with female gender identity Ross 2009, 2015), liberal political identity (Kaikati et al 2017), and from a lower social class (Piff et al 2010) have been found to demonstrate higher levels of prosocial behavior.…”
Section: Individual Selfmentioning
confidence: 99%